A auriculoterapia no controle da ansiedade e do estresse - Jales, Renata Dantas (2020)
Introduction: postmodernity requires a critical conscience from the individual and consequently changes in the educational sector, contributing to the triggering of mental health problems in teachers, a fundamental part in the formation of this awareness. Auriculotherapy is an easy-to-apply practice that can act on these conditions, benefiting this professional class. Objective: to analyze the effect of auriculotherapy on the anxiety and stress scores of elementary school teachers I and II and the EJA of the Municipal School of Elementary Education Antônio Santos Coelho Neto. Methodology: before and after intervention study, approved by the Ethics and Research Committee of the Federal University of Paraíba under CAAE: 16803119.3.0000.5188. Five data collection instruments were applied, three semi-structured questionnaires (Appendices A, B and E) and two scales (Hamilton's anxiety scale and perceived stress scale). The study sought to cover the entire teaching population, but when applying the exclusion criteria, a quantitative of 20 participants was obtained, of these 09 missed two or more consecutive sessions, so the data collected from 11 teachers were analyzed, they were organized in statistical spreadsheets and analyzed through descriptive analysis, Tukey's test, ANOVA and Wald. Results and discussion: the majority, 81.8%, were female, 63.6% were between 51 and 55 years old and had a monthly income greater than four minimum wages. With regard to professional aspects, the majority, 63.6%, teach between 10 and 30 years of age, 91.9% have graduate degrees, 81.8% teach in two shifts and 54.5% work in two teaching institutions. teaching. The auriculotherapy technique had a statistically significant effect on anxiety from the second application of the Hamilton scale and on stress from the third application of the perceived stress scale, with anxiety the effect was greater in teachers who worked in more than one institution education. Final considerations: auriculotherapy successfully reduced stress and anxiety scores, contributed to the improvement of the main symptoms of these mental health problems and promoted self-perception